The set of the homogeneous linear reciprocal block maps - H.H. Al-Ka’bi, Alaa (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
In this paper ,we introduce new definition for set of the block maps reciprocal via block maps linear homogeneous ,inhomogeneous ,odd and even . while The classical definition is